2014
DOI: 10.12736/issn.2300-3022.2014413
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Operation of Low Voltage Microgrids

Abstract: The article describes the possibilities of LV microgrids operation in the island mode. Control strategies of energy sources connected to the grid by means of invertors are discussed, either for a microgrid connected to the supplying network or during the island mode operation. The presented results of research were conducted at the Laboratory of Distributed Generation at Lodz University of Technology. The study was performed for two variants of reference voltage source: the battery storage and microturbine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a small-scale active networks, such as the one under study, there are two controllable devices which can serve as grid-forming unit: MT and ESS. Studies [20] shown that in case of ESS the values of voltage amplitude and its frequency significantly depend on generated or consumed power. MT is the better source of reference voltage, as it provides more stable power supply conditions (its static characteristics are stiffer) over a wider load range.…”
Section: A Control Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In a small-scale active networks, such as the one under study, there are two controllable devices which can serve as grid-forming unit: MT and ESS. Studies [20] shown that in case of ESS the values of voltage amplitude and its frequency significantly depend on generated or consumed power. MT is the better source of reference voltage, as it provides more stable power supply conditions (its static characteristics are stiffer) over a wider load range.…”
Section: A Control Strategymentioning
confidence: 99%
“…MT is the better source of reference voltage, as it provides more stable power supply conditions (its static characteristics are stiffer) over a wider load range. Commercially available CHP can be controlled in both P-Q and U-f modes, however the change from P-Q to U-f control takes a few minutes [20], [21]. The MT is stopped when the supplying voltage fails, then it can be started in stand-alone mode only after this time period.…”
Section: A Control Strategymentioning
confidence: 99%
“…It is reasonable therefore for RES to follow a P – Q strategy to maximise output power independently of the MG operation mode. What is more, in commercially available CHP's, the change from P – Q to U – f control, although possible, cannot be performed without interruption, because the MT is stopped when the voltage falls and can begin operating in autonomous mode only after a few minutes [30, 31].…”
Section: Introductionmentioning
confidence: 99%